Dynamics of Islamic Legal Theory (Ushul al-Fiqh) toward Addressing Challenges of Halal Products in the 21st Century - Mas'ud, Ibnu; Fahmi, Arsyad Ali; Saputra, Andika (International Journal of Islamic Thought and Humanities, 2025)
The worldwide halal industry has seen quick development within the 21st Century, went with by developing complexities driven by the globalization of supply chains, troublesome mechanical developments such as hereditary building, cell-based meat, and nanotechnology, as well as the expansion of halal items into non-food divisions such as beauty care products, pharmaceuticals, and advanced fund. These complexities demand legitimate Islamic direction that's both significant and versatile. This report analyzes the part of Usul al-Fiqh, the foundational strategy of Islamic law, that tends to modern challenges in halal item advancement. Utilizing a basic and efficient writing survey of legitimate scholarly sources and investigations of fatwas issued by driving Islamic education, this report analyzes how standards of Usul al-Fiqh—including Qiyas, Istihsan, Maslahah Mursalah, Istishab, Sadd al-Dhara'i', and 'Urf, guided by Maqasid al-Shariah—are connected to address developing issues. The key discoveries highlight the versatility of the Usul al-Fiqh system in standing up to present-day challenges while uncovering noteworthy impediments such as the harmonization of worldwide measures, confirmation over complex supply chains, and the need for integration with cutting-edge logical information. The part of advances such as DNA analysis and blockchain as confirmation devices is also investigated. Contrasts of supposition (ikhtilaf) among modern researchers are analyzed as a reflection of the energetic nature of ijtihad. The report concludes that Usul al-Fiqh remains a pertinent methodological and moral system inside present-day halal talk, although it requires persistent improvement and integration to react successfully to future challenges.